DOI: 10.17077/etd.5lyxogsx
|View full text |Cite
|
Sign up to set email alerts
|

Separation of endogenous fluorophores in normal and cancer cells

Abstract: who started the separation project and Carrie Fisk for her input. I have learned a lot from everyone and their encouragement is irreplaceable. Thanks to Dr. Jim Jung-Ching Lin and Alissa van Winkle for helping us to establish the cell culture facility in Geng lab. Thanks to the Center for Biocatalysis and Bioprocessing for awarding me the graduate fellowship from 2006 to 2009. I wish to thank my aunt, Guoqing Lan, who lost her life to colon cancer in 2007, for encouraging me to go further with cancer diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 135 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…1(f)) where and an additional maximum around 420 nm for healthy tissue fluorescence is distinguishable and could be attributed to collagen and its cross-links. For the maxima of NAD(P)H there is no prominent red spectral shift, the only difference between the spectra of cancerous and healthy fluorescence for this maxima is in the intensity, which is lower for cancerous tissues fluorescence and it was already observed [11,28,38].…”
Section: Resultsmentioning
confidence: 77%
“…1(f)) where and an additional maximum around 420 nm for healthy tissue fluorescence is distinguishable and could be attributed to collagen and its cross-links. For the maxima of NAD(P)H there is no prominent red spectral shift, the only difference between the spectra of cancerous and healthy fluorescence for this maxima is in the intensity, which is lower for cancerous tissues fluorescence and it was already observed [11,28,38].…”
Section: Resultsmentioning
confidence: 77%
“…Autofluorescence images (AFI) are used for polyp differentiation based on the analysis of the autofluorescence spectra, as changes are observed between adenomas and normal mucosa because of the biochemical and morphological tissue alterations during cancerous transformation (8,9) . In this manner, endogenous fluorophores and their role as intrinsic biomarkers offer an exceptionally powerful tool for characterizing, in real time, even subtle changes of interconnected morphological and metabolic properties of cells and tissues under physiological or altered conditions (10) .…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that this methodology is amazingly robust, allowing one the flexibility to use different excitation wavelengths or solvents for CE versus fluorescence spectroscopy. The potential of this methodology for biological applications has been demonstrated by the work of my colleague Dr. Ye Li using mixtures of the universal endogenous fluorophores nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD)[101]. This opens the path for applying 2D hetero-correlation to cell extracts and tissue samples so that the identity of their hypothesized components could be confirmed.…”
mentioning
confidence: 99%